2013
DOI: 10.3109/09638237.2013.841873
|View full text |Cite
|
Sign up to set email alerts
|

Carers of forensic mental health in-patients: What factors influence their satisfaction with services?

Abstract: Carer satisfaction with forensic mental health services is likely to be higher with services that address carers' information needs. New ways of providing this information may offer greater opportunities for working with carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…While many carers rated high levels of satisfaction with contact or ability to contact the therapist (primary treating clinician), the majority of responses to satisfaction with the mental health services showed the carers were dissatisfied. Consistent with findings reported for carers not necessarily identified as mental health professionals (Macinnes et al, ; Valentini et al, ), the carers in our sample were dissatisfied with the communication between services and themselves. Research has shown that access to services is facilitated by carer knowledge and health professionals actively involving carers in planning (Dawson et al, ), yet few of our carers reported satisfaction with information sharing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While many carers rated high levels of satisfaction with contact or ability to contact the therapist (primary treating clinician), the majority of responses to satisfaction with the mental health services showed the carers were dissatisfied. Consistent with findings reported for carers not necessarily identified as mental health professionals (Macinnes et al, ; Valentini et al, ), the carers in our sample were dissatisfied with the communication between services and themselves. Research has shown that access to services is facilitated by carer knowledge and health professionals actively involving carers in planning (Dawson et al, ), yet few of our carers reported satisfaction with information sharing.…”
Section: Discussionsupporting
confidence: 90%
“…Carers often report difficulty accessing mental health services for relatives (Olasoji, Maude, & McCauley, ) with access being facilitated by carer knowledge and health professionals actively involving carers in planning (Dawson et al, ). For carers of relatives in forensic mental health services, the amount of information provided by the services was strongly associated with level of satisfaction with the services (Macinnes, Beer, Reynolds, & Kinane, ). While the use of involuntary hospitalization for mental health problems is a controversial issue in psychiatry, our research has shown that more individuals would favour involuntary admission if a family member were experiencing psychotic symptoms or suicidal intentions (Joa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the mean total satisfaction score was 23.46/25, or 93.84%. The result indicated that the families surveyed were very satisfied with the mental health inpatient services, which is consistent with some other studies [18, 19]. Gigantesco studied 105 relatives of psychiatric inpatients in Rome, Italy, and they reported a satisfaction score of 45.7/66, or 69.2% [17].…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the findings of Gigantesco et al (2002), delivering appropriate information was strongly associated with carers’ satisfaction. Additionally, they found that parents were more dissatisfied than other carers [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although not the primary aim of this study, this work has also highlighted the experiences of the family carers of patients within FIDD services. Research has examined the experiences of family carers of patients admitted to specialist inpatient intellectual disability services (James, 2015; Longo and Scior, 2004), ID services within mainstream mental health (Donner et al, 2010; Longo and Scior, 2004), generic forensic mental health services (Macinnes et al, 2013; Support in Mind Scotland, 2014) and prison (e.g. Talbot et al, 2015).…”
Section: Discussionmentioning
confidence: 99%